High oral carriage of multidrug resistant Gram-negative bacilli in adolescents: the SOPKARD-Junior study - Katkowska, Marta; Garbacz, Katarzyna; Kwapisz, Ewa; Suligowska, Klaudia; Kusiak, Aida; Cichońska, Dominika; Świetlik, Dariusz (Frontiers in Cellular and Infection Microbiology, 2023)
The colonization of the oral cavity by potentially pathogenic antimicrobial-resistant bacteria in adolescents and its consequences is very poorly understood. The present study focused on the occurrence of oral colonization by Gram-negative bacilli (GNB) and their multidrug resistance, including the production of extended-spectrum β-lactamases (ESBLs) and carbapenemases, among healthy adolescents and risk factors associated with GNB colonization.This study was conducted as part of "A program for the early detection of risk factors for lifestyle diseases SOPKARD-Junior". Oral samples were collected from 182 adolescents from four public elementary schools in Sopot, Poland, aged 13-14 years. Bacterial strains were identified by the MALDI-TOF MS method. The NG-Test® CARBA-5 was used to detect and differentiate the five most widely distributed carbapenemases. Demographic and clinical data were collected and statistical analysis of risk factors was performed. A total of 68 out of 182 (37.4%) healthy adolescents was documented oral colonization with Gram-negative bacilli, including 50/182 (27.5%) multidrug resistant (MDR-GNB) strains. Over 60% of oral carriage concerned three main genera Enterobacter spp., Pseudomonas spp., and Serratia spp., which were detected in 22.1%, 19.1%, and 19.1% of participants, respectively. Citrobacter spp., This is a provisional file, not the final typeset article Escherichia coli, Klebsiella spp., Hafnia spp., Aeromonas spp., Acinetobacter spp., and Stenotrophomonas spp. were also isolated. The antimicrobial resistance to ampicillin (100%), ceftazidime (69.1%), meropenem (60.3%), gentamycin (60.3%), piperacillin/ tazobactam (52.9%), and piperacillin (45.6%) were the most common. Among 73.5% GNB strains multidrug resistance was observed, including all Pseudomonas spp. strains. Among MDR-GNB, 30.4% were resistant to four groups of antibiotics, half of the MDR Pseudomonas spp. strains were resistant to 10 groups of antibiotics. Extended-spectrum β-lactamases were produced by Enterobacter cloacae, Klebsiella spp., and Serratia spp. (7.4%). Colonization by ESBLs-positive GNB strains was significantly associated with recurrent respiratory infections, nasal congestion, and bronchitis (p<0.05).Our study revealed high oral carriage of multi-drug resistant Gram-negative bacilli in healthy adolescents and the association of ESBL-producing strains with respiratory infections. Further studies on oral colonization with GNB are necessary due to the possibility of distinct infections and the acquisition of antibiotic resistance by resident microbiota.